The intelligent technologies application in modelling of military task - Pincevičius, Albertas (Lietuvos matematikos rinkinys, 2011)
By using information bases of Geographic Information Systems (GIS) and the system of computer algebraMAPLE, created system for planning military actions and estimating capabilities of a military unit to execute a certain task. Using GIS it possible to carry out the engineer estimation of the terrain. A visibility instrument has been created which indicates visibility on the battlefield from several chosen terrain places. Actions of each individual soldier on the battlefield are modeled, the impact of random factors is estimated and a “digital experiment” of a would-be attack is carried out and results represented on the map.